Zagadnienie charakteru narodowego w krytyce literackiej Stanisława Tarnowskiego - Stachura-Lupa, Renata (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2019)
The article addresses the issue of functioning in the literary criticism of the second half of the 19th century of the category of „national spirit”, which is an expression of belief in the existence of the phenomenon of national characters in the world. For Tarnowski, the relationship between literature and the „spirit” of the nation is indisputable and remains in connection with his concept of history (as God’s domain) and the place of individuals in society. Art comes from the need for ideals, especially the ideal of beauty, which were inscribed in human nature by God. For Tarnowski, the artist is both an individual and a product of the national „spirit”. By creating, it expresses the character and moral condition of the nation at a given historical moment. Works (especially masterpieces) can, in turn, affect the shape of the socio- spiritual life of the nation, and thus to some extent and shape its character. In his thinking about the relationship between literature and literary criticism and the nation, Tarnowski remains faithful to idealistic aesthetics.